Evaluating Public Policy Interventions for Out-of-School Children from Administrative and Political Perspectives: Evidence from Gorontalo Province - Prasaja Arifiyanto; Rauf A. Hatu; Ismet Sulila; Yanti Aneta (Universitas Teuku Umar, 2026)
This study aims to evaluate the policy for handling out-of-school children in Gorontalo Province by examining its implementation, governance mechanisms, and contextual challenges at the local level. The research employs a qualitative phenomenological approach to capture the perspectives, experiences, and interpretations of key actors involved in education policy implementation. Data were collected through in-depth interviews, document analysis, and field observations involving provincial and district education officials, school principals, teachers, local government representatives, parents, and children who had dropped out of school. The data were analyzed interactively using stages of reduction, display, and conclusion drawing, with policy evaluation focused on administrative, legal, and political dimensions. The findings indicate that the problem of out-of-school children in Gorontalo Province is most prominent among adolescents aged 16–18 years, particularly during the transition to secondary education. Economic pressure, socio-cultural norms, geographic accessibility, and limited educational infrastructure are key determinants of school discontinuation. From an administrative perspective, weaknesses in data integration and cross-sectoral coordination reduce policy effectiveness. Legally, although the policy framework is relatively strong, weak law enforcement and the absence of clear sanctions limit its coercive power. Politically, formal government support has not been fully translated into responsive and participatory policies for vulnerable groups. In conclusion, the effectiveness of policies addressing out-of-school children in Gorontalo Province depends not only on program availability but also on strengthening governance capacity, legal enforcement, and collaborative, context-sensitive implementation.